Author Correction: Selection of suitable reference genes for gene expression studies in myxosporean (Myxozoa, Cnidaria) parasites - Kosakyan, Anush; Alama-Bermejo, Gema; Bartošová-Sojková, Pavla; Born-Torrijos, Ana; Šíma, Radek; Nenarokova, Anna; Eszterbauer, Edit; Bartholomew, Jerri; Holzer, Astrid S (Scientific reports, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.